2002
DOI: 10.1007/s00066-002-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Proton Radiation Therapy for Pediatric Low-Grade Astrocytomas

Abstract: This report on pediatric low-grade astrocytomas confirms proton radiation therapy as a safe and efficacious 3-D conformal treatment modality. Results are encouraging for central tumors as well as large optic pathway tumors, where dose conformity is of particular importance; yet it is difficult to achieve. Longer follow-up time is needed to fully evaluate the benefits of normal tissue sparing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 28 publications
0
65
0
3
Order By: Relevance
“…(The dose distribution for a child with medulloblastomas undergoing craniospinal irradiation with protons is shown in Figure 2.) LLU investigators reported a reduction in acute toxicity with the treatment of three children with medulloblastoma treated with craniospinal irradiation using the proton beam technique (Yuh et al, 2004). Loma Linda investigators also evaluated proton beam irradiation in the treatment of paediatric patients with intracranial low-grade astrocytoma (Hug et al, 2002a). Between 1991 and 1997, 27 patients underwent fractionated proton radiation therapy for progression of recurrent low-grade astrocytoma.…”
Section: Paediatric Malignanciesmentioning
confidence: 99%
“…(The dose distribution for a child with medulloblastomas undergoing craniospinal irradiation with protons is shown in Figure 2.) LLU investigators reported a reduction in acute toxicity with the treatment of three children with medulloblastoma treated with craniospinal irradiation using the proton beam technique (Yuh et al, 2004). Loma Linda investigators also evaluated proton beam irradiation in the treatment of paediatric patients with intracranial low-grade astrocytoma (Hug et al, 2002a). Between 1991 and 1997, 27 patients underwent fractionated proton radiation therapy for progression of recurrent low-grade astrocytoma.…”
Section: Paediatric Malignanciesmentioning
confidence: 99%
“…In small series, it has been found to be well tolerated; however, it is not widely available to patients and has not proven to be superior to standard techniques. 27,65 Current recommendations state that children younger than 7 years of age should receive chemotherapy as first-line treatment. Children between the ages of 7 and 10 years fit into a gray zone of patients who may or may not warrant radiation therapy, and patients older than 10 years should be treated with [45][46][47][48][49][50] Gy in fractions of 160-200 cGy each.…”
Section: Radiotherapy For Opgsmentioning
confidence: 99%
“…Hug et al [14] evaluated the safety and efficacy of proton therapy for 27 patients with progressive or recurrent intracranial LGG, treated between 1991 and 1997 at Loma Linda University Medical Center. Fifteen patients had diencephalic tumors, seven had cerebral and cerebellar hemispheres tumors and in five the tumor was located in the brainstem.…”
Section: Low-grade Gliomasmentioning
confidence: 99%